Food Security in India: Milestones Achieved So Far - Jyoti Chaudhary; Kalpna Thakur; Rohit Shelar; Rajat Singh; Rimpika; Sarita Devi; Swati Verma (Archives of Current Research International, 2024)
World hunger is one of the major challenges, across globe; up to 828 million people do not have enough food and 49 million people facing emergency level of hunger. Being the most populous country of the world, India has achieved steady economic growth and the production of the foodgrains has increased however 21.25 per cent of the population lives on less than US1.90 a day. Over the past seven decades the growth in the area and production of the foodgrains was 0.19 % and 2.37 % per annum respectively. The per capita availability of the foodgrains has increased to 185.4 Kg per annum with growth rate of 0.15 per cent from 1951 to 2021. The availability of the foodgrains has increased due to the improvement in the various government schemes like Targeted Pubic Distribution System (TDPS) with the joint efforts of World food programs. Further the country has achieved a lot in terms of the foodgrains export as it increased to Rs. 3759.09 billion during 2021-22 from Rs. 60.13 billion during 1990-91. The country still suffers from hunger and malnutrition. The reason being the poor people still have limited access to these commodities in the country. Increasing the rural and urban employment along with the self employment can increase the access to the food. Thus government needs to focus more on the food accessibility and make available the nutrition rich food to the population.